2000
DOI: 10.4049/jimmunol.164.1.404
|View full text |Cite
|
Sign up to set email alerts
|

fMet-Leu-Phe Stimulates Proinflammatory Cytokine Gene Expression in Human Peripheral Blood Monocytes: The Role of Phosphatidylinositol 3-Kinase

Abstract: The fMLP-stimulated release of proinflammatory cytokines such as IL-1 by human peripheral blood monocytes is an important component of the inflammatory process. The signaling mechanisms used by fMLP to stimulate the release of cytokines are still incompletely understood. We previously demonstrated that fMLP-stimulated NF-κB activation in PBMC and now we present evidence that the lipid products of phosphatidylinositol 3-kinase (PI 3-kinase) are required for fMLP-stimulated activation of NF-κB. Pretreatment with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
49
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 48 publications
1
49
0
Order By: Relevance
“…Monocytes-We have previously demonstrated that fMLP stimulated PI3K activity, and this activity is required for fMLP-induced NF-B activity in human monocytes (13). Based on our current results and our previous report, the relationship between PI3K activation and activation of the RhoA appears to be an important issue.…”
Section: Effects Of Pi3k Inhibitors On Fmlp-induced Rhoa Activation Imentioning
confidence: 56%
See 2 more Smart Citations
“…Monocytes-We have previously demonstrated that fMLP stimulated PI3K activity, and this activity is required for fMLP-induced NF-B activity in human monocytes (13). Based on our current results and our previous report, the relationship between PI3K activation and activation of the RhoA appears to be an important issue.…”
Section: Effects Of Pi3k Inhibitors On Fmlp-induced Rhoa Activation Imentioning
confidence: 56%
“…We previously demonstrated that fMLP-induced NF-B activation required PI3K activity in human monocytes (13), and here we present evidence that RhoA activity is essential for fMLP-induced NF-B activation. To test the possibility that PI3K is a component of the fMLP-stimulated signaling pathway leading to RhoA activation, we assessed the effect of inhibiting PI3K activity on subsequent fMLP-induced RhoA activation.…”
Section: Effects Of Pi3k Inhibitors On Fmlp-induced Rhoa Activation Imentioning
confidence: 62%
See 1 more Smart Citation
“…However, some reports suggested that class IA PI3K might also be activated by GPCRs and may play a role in chemokine receptor-mediated IL-1␤ induction in primary human monocytes (35)(36)(37)(38). To define the role of specific PI3K isoforms on gp120-stimulated IL-1␤ release, we used the class IA PI3K-specific inhibitor PI-103 (39) and the class IB PI3K specific inhibitor AS605240 (40,41).…”
Section: Activation Of Pi3k Is Necessary For Gp120-triggered Il-1␤ Inmentioning
confidence: 99%
“…NF-B is of considerable importance in immune cell function because of its ability to activate the transcription of many proinflammatory immediate early genes, and we have shown that it can be activated by chemoattractants such as fMLP (1)(2)(3)(4). Indeed, the fMLP-induced activation of NF-B appears essential for proinflammatory cytokine synthesis in human peripheral blood monocytes (5).…”
mentioning
confidence: 99%